2015
DOI: 10.1039/c5cp00924c
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticle array formation on dimpled Ta templates using pulsed laser-induced thin film dewetting

Abstract: Here we show that pulsed laser-induced dewetting (PLiD) of a thin Au metallic film on a nano-scale ordered dimpled tantalum (DT) surface results in the formation of a high quality Au nanoparticle (NP) array. In contrast to thermal dewetting, PLiD does not result in deformation of the substrate, even when the Au film is heated to above its melting point. PLiD causes local heating of only the metal film and thus thermal oxidation of the Ta substrate can be avoided, also because of the high vacuum (low pO2) envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…However, substrate deformation due to the extended exposure at high temperatures needed for the dewetting of high-melting-point metals limits its use mainly to low-melting-point metals. 24,25 In addition, there are potential metal-substrate chemical interactions and metal diffusion into the substrate, complicating the dewetting process. 26 An alternative dewetting technique is liquid-state dewetting induced by pulsed laser irradiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, substrate deformation due to the extended exposure at high temperatures needed for the dewetting of high-melting-point metals limits its use mainly to low-melting-point metals. 24,25 In addition, there are potential metal-substrate chemical interactions and metal diffusion into the substrate, complicating the dewetting process. 26 An alternative dewetting technique is liquid-state dewetting induced by pulsed laser irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…29 As a result, the PLiD method prevents any detrimental effect to the underlying substrates, thanks to the instantaneous heating within the short width of laser pulses. It is therefore suitable for making NPs of high-melting-point metals such as Pt, 30 Fe, 31 and Co-Pt, 32 in addition to lowmelting-point metal NPs, e.g., Au, 24,33 Ag, 33,34 and Cu. 27,35 PLiD via liquid-state dewetting is able to produce spatially ordered metal NPs, which have more uniform distributions than those obtained from solid-state thermal dewetting.…”
Section: Introductionmentioning
confidence: 99%
“…Recently laser‐assiated methods have become a powerful platform for plasmonic nanostructures fabrication and tuning . More specifically, it has recently been experimentally demonstrated that asymmetric hybrid metal‐dielectric (Au/Si) nanoparticles consisting of a gold (Au) nanodisk placed on an upper base of truncated silicon (Si) nanocone, can be tuned via fs‐laser induced melting at the nanometer scale .…”
Section: Introductionmentioning
confidence: 99%
“…67,69 Fine control of the NP size can thus be achieved by film thickness and substrate topography. 42,68,7077 …”
Section: Templated Dewettingmentioning
confidence: 99%
“…76,77 This method allows also for dewetting of high melting point metals and avoids substrate deterioration ( e.g. , by thermal oxidation).…”
Section: Templated Dewettingmentioning
confidence: 99%